Upaya Guru BKI dalam Membentuk Akhlak Siswa di MTs Darullughah Wadda’wah Bangil - Husairi, Husairi; Felayati, Roikhan Ali (Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan Jawa Timur, 2022)
Schools are centers of change, both changes in ways of thinking and changes in behavior. One of the main factors in preserving the Islamic way of life is incorporating Islamic values into the education system. Islam views morals as very important in life. The inclusion of Islamic counseling guidance in educational programs is felt necessary to help students so that they can be better at learning and personality, including developing student morals. Based on the results of the research, it can be concluded that the Islamic guidance and counseling program at MTS Darullughah Wadda'wah Bangil has 2 programs, namely an annual program and an additional program. The counseling guidance approach at MTS Darullughah Wadda'wah Bangil has different approaches, including a preventive approach, a remedial approach, and a behavioral approach. The student response to counseling guidance at MTS Darullughah Wadda'wah Bangil was a positive response, from the supervising teacher said that the students were very enthusiastic about following the guidance.